Metode Penugasan melalui pembelajaran IPS untuk Meningkatkan Hasil Belajar Siswa - Fadhli Dzil ikrom (Amal Insani Foundation, 2024)
Researchers use the Classroom Action Research (PTK) or Classroom Action Research method to make it easier to prepare research according to the title